Hepatitis C vaccine: supply and demand. - Strickland, G; El-Kamary, S; Klenerman, P; Nicosia, A (2008)
Despite difficulties associated with extreme variability and mutability of hepatitis C virus (HCV), several vaccines that prevent initial infection or viral persistence, or that clear viraemia in individuals with chronic HCV infections, are currently in development. At least one vaccine that may prevent chronic persistent infections will soon be available for testing. We review the widespread importance of HCV infection and disease, the immune response to HCV and correlates of protection, prevention strategies and vaccine candidates, and groups that will need the vaccine and provide suitable populations for assessing vaccine safety and efficacy. The evaluation of prophylactic vaccines is particularly problematic since distribution must focus upon individuals at high risk of exposure-for example, intravenous drug users and health-care providers in areas with high HCV prevalence. Although there is a huge need for therapeutic vaccines, further immunological hurdles must be cleared before one becomes available.